Effect of Halotolerant Microbial Inoculants on Growth and Yield Attributes of Groundnut (Arachis hypogaea L.) under Varying Soil Salinity Levels in Dry Land Condition - , Gandikota Rupa Lalitha; , N. Chandra Sekaran; , D. Selvi; , T. Kalaiselvi; , B. Gokila; , D. Jayanthi (Archives of Current Research International, 2025)
A pot culture experiment was conducted to assess the influence of microbial bio-stimulants CSR-GROW-SURE and TNAU culture (Bacillus subtilis) on the growth, nodulation, and no. of pods plant-1 of groundnut (var. CO7) under saline soil conditions (EC: 4.03, 5.01, and 6.02 dS m-1) maintained at 75 % field capacity (FC). The microbial cultures were applied at 1, 2, and 3 L ha-1. The results revealed that both bio-inoculants significantly enhanced plant growth attributes, with higher values observed at the post-harvest stage. Comparing treatments, the maximum values are recorded in CSR-GROW-SURE and TNAU cultures with 3 L ha-1, and while comparing, all salinity levels, the 4.03 dS m-1 soil recorded maximum values compared to 5.01 and 6.02 dS m-1 soils in all parameters. Furthermore, the interaction of treatments with various salinity levels of soil indicated that the treatments CSR-GROW-SURE with 3 L ha-1 and TNAU cultures with similar dosage at 4.03 dS m-1 produced the increase in percentage of plant growth and yield attributes than treatment control. The treatment CSR-GROW-SURE with 3 L ha-1 recorded the percentage increase of germination (94.47 %), root length (10.83 cm), number of nodules plant-1 (15.67) and number of pods plant-1 (17.00) over control. And the treatment TNAU culture with 3 L ha-1 is statistically on par with germination percentage (94.02 %), root length (10.78 cm), nodules plant-1 (15.67) and pods plant-1 (17.00) compared to control. The observed benefits are due to microbial production of phytohormones (IAA, gibberellins), ACC deaminase, siderophores, nitrogen fixation, and zinc solubilization. These findings strongly support the application of halotolerant microbial bio-stimulants as a sustainable strategy to mitigate salinity stress and enhance groundnut productivity in dryland saline agro-ecosystems.